THE ROLE OF SOCIAL MEDIA IN INCREASING MSME INCOME: A CASE STUDY IN SUMPANG BINANGAE VILLAGE, BARRU REGENCY - Resky Nur Fadillah; Andi Rachmat (Meraja journal, 2025)
[Full Paper] to pdf Copyright (c) 2025 Meraja journal